New Perspectives in Amblyopia Therapy on Adults: A Critical Role for the Excitatory/Inhibitory Balance - Baroncelli, Laura; Maffei, Lamberto; Sale, Alessandro (Frontiers in Cellular Neuroscience, 2011)
Amblyopia is the most common form of impairment of visual function affecting one eye, with a prevalence of about 1% to 5% of the total world population. This pathology is caused by early abnormal visual experience with a functional imbalance between the two eyes owing to anisometropia, strabismus or congenital cataract, resulting in a dramatic loss of visual acuity in an apparently healthy eye and various other perceptual abnormalities, including deficits in contrast sensitivity and in stereopsis. It is currently accepted that, due to a lack of sufficient plasticity within the brain, amblyopia is untreatable in adulthood. However, recent results obtained both in clinical trials and in animal models have challenged this traditional view, unmasking a previously unsuspected potential for promoting recovery after the end of the critical period for visual cortex plasticity. These studies point toward the intracortical inhibitory transmission as a crucial brake for therapeutic rehabilitation and recovery from amblyopia in the adult brain.